PENANGGULANGAN KOROSI PADA PIPA GAS DENGAN METODE CATODIC PROTECTION (ANODA KORBAN) PT PGN SOLUTION AREA TANGERANG - Redaksi Tim Jurnal (JURNAL POWERPLANT, 2017)
Corrosion is a common problem that often occurs in metals. Corrosion is the damage or degradation of metal due to the redox reaction between a metal with various substances in the environment that produce undesirable compounds. In the event of corrosion, the metal will experience oxidation while the air will experience reduction. Corrosion can be regarded as an electrochemical event between the metal and its environment. Simply, corrosion can occur if there are anodes, cathodes, electrolyte solutions, and metallic contacts between the cathode and the anode. In submarine pipelines, corrosion problems occur frequently for a corrosion-control measure. One of them is by using cathodic protection method using sacrificial anode system (sacrificial anode) and system impressed current (tilt current)